Teatralidades para infâncias confinadas: jogos, narrativas e outras poéticas visuais (Revista NUPEART, 2020)
This experience report narrates, describes and comments about the paths that led to the creation of a technovivial theatrical experiment, experienced with children between the ages of 7 ans 12, from virtual meetings held by videoconference. Creative practices were proposed, through statements experienced collectively with a group of 10 participants, during the period of 1 hour. Such statements were guided by the reinvention of proposals that were inspired by theatrical games, improvisation exercises, storytelling practices and had as a raw material the "children relationship with playing". This creative proposal emerged in the context of social isolation, which began to permeate everyday life, on a world scale, in the year of 2020. The text contributes to unveiling the invented paths and some reflections made towards a creative practice that thinks about the relationship between the child and the creative use of technology.